Indigenous Knowledge Systems for development: A critical analysis from Nkayi District, Zimbabwe - Zikhali, Whitehead (Advances in Social Sciences Research Journal, 2018)
Local and indigenous knowledge refers to the understandings, skills and philosophies developed by societies with long histories of interaction with their natural surroundings. For rural and indigenous people, local knowledge informs decision-making about fundamental aspects of day-to-day life. This knowledge is integral to a cultural complex that also encompasses language, systems of classification, resource use practices, social interactions, ritual and spirituality. These unique ways of knowing are important facets of the world’s cultural diversity and provide a foundation for locally-appropriate sustainable development (UNESCO, 2017). This paper argues that development is an end which people in the global south seek in the context of a dynamic environment characterised by contesting systems of power. Basing from evidence in Nkayi, an area in western Zimbabwe, the paper deploys Foucauldian lens to reveal contesting systems of knowledge in rural Zimbabwe. In these communities, community members employ a mix of knowledge systems to attaint their forms of ‘development’. The paper reveals that development is not a zero-sum game where the use of western knowledge means complete neglect of indigenous knowledge and vice versa. From the analysis made, the author recommends that a nuanced appreciation of knowledge structures be made by development practitioners and policymakers prior to either embracing or dismissing them. Even then, it cautions against wholly labelling systems of knowledge either indigenous or western due to the cross-pollination which has transpired over time.